2012
DOI: 10.1002/qua.24315
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the confinement of methane in water clusters

Abstract: A search for stable local minima CH 4 -(H 2 O) n closed methane clathrates was done at the xB97X-D/aug-cc-pVDZ level of the theory, for n up to 20, starting from various different configurations for each size. The reliability of the method was validated by comparison to the complete basis set limit (CBSL) values of the methane-water interactions, of the water-water interactions and of the binding energies of (H 2 O) 20 clusters. A potential model fitted to reproduce the CBSL interaction energy of the optimal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
4
11
0
Order By: Relevance
“…There have been numerous theoretical studies of the interactions between host water cages and small guest molecules, , using functionals including revPBE, B3LYP, , B3LYP-D2, ,,, M05-2X, M06-L, M06-HF, M06-2X, B97-D2, ,, ωB97X-D, and vdW-DF . Small-basis Hartree–Fock and MP2 calculations have also been reported for these systems. ,,, Despite this considerable computational effort, there has been no attempt to benchmark the computed interaction energies with respect to high-quality ab initio calculations.…”
Section: Results For Clustersmentioning
confidence: 99%
“…There have been numerous theoretical studies of the interactions between host water cages and small guest molecules, , using functionals including revPBE, B3LYP, , B3LYP-D2, ,,, M05-2X, M06-L, M06-HF, M06-2X, B97-D2, ,, ωB97X-D, and vdW-DF . Small-basis Hartree–Fock and MP2 calculations have also been reported for these systems. ,,, Despite this considerable computational effort, there has been no attempt to benchmark the computed interaction energies with respect to high-quality ab initio calculations.…”
Section: Results For Clustersmentioning
confidence: 99%
“…14 This functional proved to be robust and accurate in describing noncovalent supramolecular complexes. [15][16][17][18][19][20] Initial accuracy test for b97x-d, B3LYP, and EDF2 20,21 functionals in comparison to available X-ray structures of the Eand Zisomers of an azobenzene (AB) clearly demonstrate that b97x-d functional gave results very similar to X-ray data (at least for E-AB), whereas B3LYP and EDF2 functionals slightly overestimate the bond distance between azo nitrogen atoms (Table S2). Nevertheless, contrary to X-ray data all studied functionals predicted shorter distance of the azo linkage for Z-AB than for E-AB.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Monte Carlo large scale searches for the optimal configurations of water molecules around the methane molecule, CH 4 @(H 2 O) n for n up to 20, reported that the smallest value at which the (H 2 O) n cluster encapsulates the CH 4 molecule occurs at n = 14 . Furthermore, water molecules are tangentially oriented with respect to the methane surface in a clathrate‐like shape.…”
Section: Resultsmentioning
confidence: 99%